(untitled) (The Insight, 2025)
Introduction: Prolapsed lumbar intervertebral disc (PLID) is a leading cause of low back pain and radiculopathy, significantly influencing patients’ quality of life. ESIs reduce inflammation and nerve root irritation, offering short-term pain relief and improved mobility. Methods & Materials: This one-year retrospective study (January 2022–December 2023) at Gazi and Khulna Medical Colleges, Bangladesh, included 50 adults (20–60 years) with MRI-confirmed lumbar disc prolapse unresponsive to ≥4 weeks of conservative therapy. Patients received interlaminar or transforaminal epidural steroid injections. Pain (VAS), disability (ODI), complications, and satisfaction were evaluated at baseline, 1 week, 1 month, and 3 months. Result: The study included 50 patients with a mean age of 41.6 years; 56% were male, and 60% had sedentary occupations. The most common disc prolapse level was L4-L5 (56%), and protrusion was the predominant type (44%). Interlaminar ESI was most frequently used (60%) with methylprednisolone (64%), and 60% received a single injection. Significant reductions in pain and disability were observed, with VAS scores dropping from 7.6 to 2.8 and ODI scores from 58.2% to 24.3% at 3 months (p<0.001). Complications were minimal and mild, and 76% of participants reported excellent or good satisfaction following the intervention. Conclusion: Epidural steroid injections (ESIs) effectively manage prolapsed lumbar intervertebral disc (PLID) by providing significant pain relief and functional improvement. This study showed marked reductions in VAS and ODI scores, with minimal complications and high patient satisfaction, supporting ESIs as a safe, effective, and non-surgical treatment option for PLID.